STRENGTHENING THE ROLE OF SPECIAL SUPERVISORS (GPK) AS A MAIN PILLAR OF SUCCESS OF INCLUSION EDUCATION - Isnaini Maulida Rahmawati (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2021)
This study aims to describe the importance of optimizing the strategic role and the main task of special supervisors (GPK) in inclusive schools. An inclusive school is a formal educational institution that organizes a special education system for children who have limitations and special needs. The implementation of inclusive education can be carried out in general schools by providing a special portion of time for learning by bringing in special mentoring teachers (GPK) who are assigned to guide and provide special services on inclusive education. On the other hand inclusive education can also be held independently in a formal institution with a learning system that is constructed based on the needs of students such as SLB (Extraordinary Schools). The method used in this research is descriptive qualitative research. With this research it is expected to reveal various qualitative information with careful and meaningful analysis-descriptions. Data sources in this study include principals, special supervisors and class teachers. Data collection is done by interview, observation, and documentation. As for the data analysis techniques through the stages of data reduction, data presentation and data analysis. The context of this research is the implementation of inclusive schools in Sidoarjo district for elementary and junior high school levels. The results of the study include (a) Knowing the model of implementing inclusive education in general schools by bringing in special tutors (GPK) (b) The importance of the presence of special tutor teachers (GPK) for the success of inclusive education in accordance with MoNE Regulation No. 70 of 2009.